Accuracy of contrast-enhanced computed tomography scan in assessing depth of invasion in oral tongue squamous cell carcinoma / Chin Siok Yoong - Chin, Siok Yoong (2019)
INTRODUCTION: Depth of invasion (DOI) in oral squamous cell carcinoma is an important predictor of locoregional spread, distant metastasis, disease recurrence and survival. OBJECTIVES: To compare DOI measurement between preoperative contrast-enhanced computed tomography (CECT) scan and histopathological examination (HPE) in oral tongue squamous cell carcinoma (OTSCC). To determine the correlation between CECT and HPE measurements. To determine the measurement accuracy of DOI from CECT. MATERIALS & METHODS: A retrospective study of 18 OTSCC patients in Faculty of Dentistry, University of Malaya was carried out. Preoperative CECT scans were reviewed by a single observer to measure the DOI on axial and coronal sections, then compared to HPE. Data were analysed for intraobserver reliability and strength of correlation determined using intraclass correlation coefficient (ICC). Mean DOI was compared using repeated measures ANOVA and accuracy was assessed using BlandAltman plot. RESULTS: Intraobserver reliability was excellent, with ICC=0.996 for axial and ICC=0.999 for coronal. Overall, CECT measurement of DOI was 1-2mm smaller than HPE, with mean differences of -0.743mm for axial and -1.106mm for coronal. There was excellent correlation between CECT and histopathological tumour depths in both axial (ICC=0.956) and coronal (ICC=0.965). Bland-Altman analysis showed 95% confidence interval for measurement differences between CECT and histopathological depth were within the limits of agreement, indicating that these two methods can be used interchangeably. CONCLUSION: Measurement of DOI from iv CECT in OTSCC was comparable to HPE with an average of 1-2mm decrement. There was excellent correlation in both axial and coronal views compared to HPE, with accurate DOI measurement from CECT.